Controlled Sedation with Alphaxalone-Alphadolone. Issue 5920 (22nd June 1974) - Ramsay, M. A. E.; Savege, T. M.; Simpson, B. R. J.; Goodwin, R.
Abstract : Alphaxalone-alphadolone (Althesin), diluted and administered as a controlled infusion, was used as a sedative for 30 patients in an intensive therapy unit. This technique allowed rapid and accurate control of the level of sedation. It had three particularly useful applications: it provided "light sleep, " allowed rapid variation in the level of sedation, and enabled repeated assessment of the central nervous system. Sedation was satisfactory for 86% of the total time, and no serious complications were attributed to the use of the drug. Furthermore, though alphaxalone-alphadolone was given for periods up to 20 days there was no evidence of tachyphylaxis or delay in recovery time.